Assessing the insights on experiential learning using the augmented reality exploration - Abdullah, Fadzidah; Kassim, Mohd Hisyamuddin; Sanusi, Aliyah Nur Zafirah; Abdul Razak, Mohd Raziff (International Organization Center of Academic Research (OCERINT), 2020)
In the tertiary educational setting, learning is often taken place in a classroom environment that is too formal. Thus, to break the norm and to make learning enjoyable, exploration of a new method of knowledge dissemination using Augmented Reality (AR) was experimented in the teaching and learning of steel construction in architectural education. This exploration is intended to initiate an active learning and enjoyable environment for students at the university level. Hence, this paper examines students' insights on their experiences of AR exploration, where they actively learn through playing, experimenting, socialising and collaborating with their peers. During the learning process, students produced virtual steel construction details models, and then visualised the models through AR application that shows an interface with real time and real space. Prior to the AR exploration, students went through a series of workshops where they collaboratively developed models of steel construction details, based on their completed research. Students' feedback was sought after they completed the projects, particularly on their impression towards the project. The collected data was in the format of verbatim, obtained by having open-ended questionnaires. The data would be analysed using qualitative methods of content analysis using atlas.ti software. The generated frequency of coded factors would be quantified to produce an empirical result. Most students positively gave feedback that the new method applied for learning is effective and exciting, and they suggested the same approach should be implemented to other courses in the architectural educational program.The AR application had also offered them to have very practical and economical techniques of active learning, with the merger of ICT and online conveniences.